2001
DOI: 10.1074/jbc.m104452200
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Intermediate of the Amyloidogenic Protein β2-Microglobulin at Neutral pH

Abstract: Aggregation and fibrillation of ␤ 2 -microglobulin are hallmarks of dialysis-related amyloidosis. We characterize perturbations of the native conformation of ␤ 2 -microglobulin that may precede fibril formation. For a ␤ 2 -microglobulin variant cleaved at lysine 58, we show using capillary electrophoresis that two conformers spontaneously exist in aqueous buffers at neutral pH. Upon treatment of wild-type ␤ 2 -microglobulin with acetonitrile or trifluoroethanol, two conformations were also observed. These conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
62
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 41 publications
5
62
0
Order By: Relevance
“…The characteristic spectrum of wild-type ␤ 2 m is compatible with ϳ50% ␤-structures (strands and turns), 50% random structure, and practically no helix structures as reported previously (4,27). The changes in the far-UV spectrum of the cleaved forms, most pronounced for the Lys 58 -␤ 2 m species, are similar to the changes in the CD spectra of wild-type ␤ 2 m obtained in 10 -15% trifluoroethanol or 20 -30% acetonitrile where there is a mixture of the native fold and a solvent-induced species with less ␤-structure and more helix structure (27). Thus the far-UV spectra of Electrophoretic Separation of ␤ 2 m and Its Cleaved Variants-When the three purified ␤ 2 m species were separated by CE, more than one peak was observed in both the Lys 58 -␤ 2 m and the des-Lys 58 -␤ 2 m preparations (Fig.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…The characteristic spectrum of wild-type ␤ 2 m is compatible with ϳ50% ␤-structures (strands and turns), 50% random structure, and practically no helix structures as reported previously (4,27). The changes in the far-UV spectrum of the cleaved forms, most pronounced for the Lys 58 -␤ 2 m species, are similar to the changes in the CD spectra of wild-type ␤ 2 m obtained in 10 -15% trifluoroethanol or 20 -30% acetonitrile where there is a mixture of the native fold and a solvent-induced species with less ␤-structure and more helix structure (27). Thus the far-UV spectra of Electrophoretic Separation of ␤ 2 m and Its Cleaved Variants-When the three purified ␤ 2 m species were separated by CE, more than one peak was observed in both the Lys 58 -␤ 2 m and the des-Lys 58 -␤ 2 m preparations (Fig.…”
Section: Resultssupporting
confidence: 50%
“…Recent data from other groups support the notion that this folding intermediate may be on the pathway to amyloid formation (25). In addition, we observed by CE that purified Lys 58 -␤ 2 m is also heterogeneous in the absence of organic solvent (27). In the present study, we characterize the Lys 58 -␤ 2 m and des-Lys 58 -␤ 2 m molecules using circular dichroism, CE, and affinity CE with heparin and Congo red.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…In the serum of uremic patients, but not in healthy subjects, the presence of intermediate misfolded forms of b2M was reported by some authors. 9 Uji et al demonstrated poor removal of intermediate forms compared with native b2M among 31 patients on HD treatment, even when the patients were treated with high-flux HD or hemodiafiltration. 10 In vitro studies showed that under physiological conditions, enhanced amyloidogenesis is observed in the presence of an increase in equilibrium concentration of a b2M intermediate form, named intermediate T (I T ), characterized by a trans isomerization of Pro32.…”
mentioning
confidence: 99%